The Production of Complement Inhibitor Proteins in Mammalian Cell Lines—Light at the End of the Tunnel? - Attila Szvetnik; Vilmos Tubak (Biomedicines, 2024)
Therapeutic recombinant proteins are powerful tools used for the treatment of many detrimental diseases such as diabetes, cancer, multiple sclerosis, rheumatoid arthritis, hepatitis, and many more. Their importance in disease therapy is growing over small molecule drugs because of their advantages like specificity and reduced side effects. However, the large-scale production of certain recombinant proteins is still challenging despite impressive advancements in biomanufacturing. The complement cascade is considered a rich source of drug targets and natural regulator proteins with great therapeutic potential. However, the versatility of such proteins has been hampered by low production rates. The recent discoveries highlighted here may bring definite improvement in the large-scale recombinant production of complement inhibitor proteins or other difficult-to-express proteins in mammalian cell lines.